TRANSMISSION TAGLINE BISMILLAH SERVES IN INCREASING THE HUMAN DEVELOPMENT INDEX (HDI) SUMENEP REGENCY EDUCATION POLICY PERSPECTIVE - Mukhlishi, Mukhlishi; Supandi, Supandi; Fadli, Moh.; Atnawi, Atnawi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
Transmission of the Tagline Bismillah Serves in Improving the Human Development Index (HDI) of Sumenep Education Policy Perspective. The location of this study, the researcher took the location or object of research on Sapudi Island, Nonggunung District, Gayam, Sakala and Pagerungan Districts, Sapeken District, and Talango. The type of research used is a qualitative research method, this research seeks to obtain information in more depth on the focus of the research. A research approach is a research plan and procedure that consists of steps based on broad assumptions as the basis for determining methods in data collection, analysis or interpretation. This approach is descriptive. The results of this study in 2018 showed that the HDI of Sumenep Regency was 0.16 points lower than that of Pamekasan. However, in 2019, the HDI of Sumenep outperformed the HDI of Pamekasan by 0.28 points. The difference between the HDI achievement of the Sumenep Regency and the HDI of Pamekasan is relatively small, namely 0.88 points in 2022. Sumenep Regency's policy can increase the level of welfare of GTT and teachers who are critical-constructive and strengthened by Education Regulations (Perbub/Perda), so that they can improve the welfare of education and get the Human Development Index. This study shows that the transmission of the tagline "Bismillah Melayani" contributes to Sumenep's HDI through education policies that are oriented towards service, equal access, and learning quality.